Diploidy for a structural gene specifying a major protein of the outer cell envelope membrane from Escherichia coli K-12. - Datta, D B (1976)
Homogenotes, heterogenotes, and intergeneric hybrids have been studied that are diploid for the structural gene of a major outer cell envelope membrane protein (protein II) from Escherichia coli. This protein can act as a phage receptor. In wild-type homogenotes, diploidy for the gene did not cause a gene dosage effect. It could be shown with two heterogenotes that both the chromosomal mutant and the episomal wild-type genes are expressed, and in each case more of the mutant than the wild-type protein species was found in the cell envelope. In on case of 21 phage-resistant mutants missing protein II was a trans effect observed of the mutant gene on the expression of the episomal wild type gene. Transfer of E. coli episomes carrying the protein II structural gene into Salmonella typhimurium and Proteus mirabilis resulted in intergeneric hybrids that became sensitive to the relevant phage and harbored the E. coli protein II in their cell envelopes. The results may be taken as suggestive evidence for a simple feedback mechanism for the regulation of synthesis of protein II, and they show that there are no highly specific requirements on protein primary structure for incorporation into an outer cell envelope membrane.